2019
DOI: 10.1002/celc.201900693
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2,2’‐bipyridyl)ruthenium(II)‐Nanomaterial Co‐Reactant Electrochemiluminescence

Abstract: Searching biocompatible electrochemiluminescence (ECL) co‐reactants for tris(2,2’‐bipyridyl)ruthenium(II) (Ru(bpy)32+), a classical ECL reagent, has attracted extensive attention to expanding its analytical applications and improving sensing performances. Advances in nanomaterial science promote the discovery of novel co‐reactants and new enhancement mechanisms for Ru(bpy)32+ ECL. In this Minireview, we discuss the current progress in Ru(bpy)32+‐nanomaterial co‐reactant ECL with an emphasis on enhancement mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Recently, some carbon-based QDs including carbon nanodots, nitrogen-doped carbon nanodots, , graphene QDs, , and so forth have been widely used as novel coreactants of the ruthenium complex because of their analogous enhancement mechanism of molecular coreactants. , Inspired by the outstanding properties such as good biocompatibility, nontoxicity, simple preparation, and excellent stability of g-C 3 N 4 QDs, we carried out the first investigation on the anodic Ru­(dcbpy) 3 2+ ECL influenced by g-C 3 N 4 QDs, as it has been reported that g-C 3 N 4 QDs played a similar coreactant role in ECL signal enhancement of the Ru­(bpy) 3 2+ system . As previous research reported, , the anodic ECL signal of the bare GCE obtained from the buffer system containing 1 mM Ru­(dcbpy) 3 2+ is relatively weak (Figure A, curve a, ∼270 a.u.).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some carbon-based QDs including carbon nanodots, nitrogen-doped carbon nanodots, , graphene QDs, , and so forth have been widely used as novel coreactants of the ruthenium complex because of their analogous enhancement mechanism of molecular coreactants. , Inspired by the outstanding properties such as good biocompatibility, nontoxicity, simple preparation, and excellent stability of g-C 3 N 4 QDs, we carried out the first investigation on the anodic Ru­(dcbpy) 3 2+ ECL influenced by g-C 3 N 4 QDs, as it has been reported that g-C 3 N 4 QDs played a similar coreactant role in ECL signal enhancement of the Ru­(bpy) 3 2+ system . As previous research reported, , the anodic ECL signal of the bare GCE obtained from the buffer system containing 1 mM Ru­(dcbpy) 3 2+ is relatively weak (Figure A, curve a, ∼270 a.u.).…”
Section: Resultsmentioning
confidence: 99%
“…The overall charge has been kept neutral to promote aggregation in polar media while the hydrophilic chains have been introduced to promote their solubility in water. While Pt-PEG is almost insoluble in water, Pt-PEG 2 is able to form a stable orange colloidal dispersion in pure aqueous solutions and its ECL performance outperforms the efficiency of the classical ECL reference [Ru(bpy) 3 ] 2+ [7,16,39].…”
Section: Aggregation-induced Electrochemiluminescencementioning
confidence: 99%
“…The overall charge has been kept neutral to promote aggregation in polar media while the hydrophilic chains have been introduced to promote their solubility in water. While Pt-PEG is almost insoluble in water, Pt-PEG 2 is able to form a stable orange colloidal dispersion in pure aqueous solutions and its ECL performance outperforms the efficiency of the classical ECL reference [Ru(bpy) 3 ] 2+ [7,16,39].…”
Section: Aggregation-induced Electrochemiluminescencementioning
confidence: 99%